2022
DOI: 10.1186/s12978-022-01413-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of contraceptive use among young Australian women with chronic disease: findings from a prospective cohort study

Abstract: Background Given chronic disease is increasing among young women and unintended pregnancies among these women are associated with poor maternal and fetal outcomes, these women would benefit from effective preconception care. However, there is a lack of understanding of how these women use or don’t use contraception to inform such interventions. This study examined patterns of contraceptive use among an Australian cohort of young women and investigated the influence of chronic disease on contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…This is important as these methods are safe for most women with chronic disease, have low failure rates and provide additional benefits during perimenopause [ 24 ]. LARC use among women with chronic disease in this cohort however was found to be substantially lower than that reported by women with chronic disease in the 1989–95 cohort at similar ages and suggests that there may be a generational shift in the perceptions surrounding the use of LARC, including the suitability of these methods for women of reproductive age with chronic disease [ 25 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is important as these methods are safe for most women with chronic disease, have low failure rates and provide additional benefits during perimenopause [ 24 ]. LARC use among women with chronic disease in this cohort however was found to be substantially lower than that reported by women with chronic disease in the 1989–95 cohort at similar ages and suggests that there may be a generational shift in the perceptions surrounding the use of LARC, including the suitability of these methods for women of reproductive age with chronic disease [ 25 ].…”
Section: Discussionmentioning
confidence: 98%
“…However, around half of the women in our study were also predicted to combine their condom use with other low efficacy methods such as withdrawal. The layering of low efficacy methods has been demonstrated among young women, including those with AICs [ 18 , 25 ]. This is particularly problematic as it has been found that 61% of women with SLE reported using these low efficacy methods and more than half reported having had an unintended pregnancy [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is important as these methods are safe for most women with chronic disease, have low failure rates and provide additional benefits during perimenopause [25]. LARC use among women with chronic disease in this cohort however was found to be substantially lower than that reported by women with chronic disease in the 1989-95 cohort at similar ages and suggests that there may be a generational shift in the perceptions surrounding the use of LARC, including the suitability of these methods for women of reproductive age with chronic disease [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, around half of the women in our study were also predicted to combine their condom use with other low efficacy methods such as withdrawal. The layering of low efficacy methods has been demonstrated among young women, including those with AICs [18, 26]. This is particularly problematic as it has been found that 61% of women with SLE reported using these low efficacy methods and more than half reported having had an unintended pregnancy [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation